2008
DOI: 10.2215/cjn.04651107
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Gram-Negative Bacteria among Patients Who Require Chronic Hemodialysis

Abstract: Background and objectives: Multidrug-resistant gram-negative bacteria are rapidly spreading throughout the world. The epidemiology of multidrug-resistant gram-negative bacteria in patients who require chronic hemodialysis has not been previously studied.Design, setting, participants, & measurements: A prospective cohort study of an outpatient hemodialysis unit was conducted. Serial surveillance cultures for multidrug-resistant gram-negative bacteria, vancomycin-resistant enterococci, and methicillin-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 21 publications
(15 reference statements)
1
86
1
4
Order By: Relevance
“…One of the methods used by various authors and authorities to characterize organisms as MDR is based on in vitro antimicrobial susceptibility test results, when they test ‘resistant to multiple antimicrobial agents, classes or subclasses of antimicrobial agents’ [9,10]. The definition most frequently used for multiresistant Gram-positive [11] and Gram-negative [1214] bacteria is ‘resistant to three or more antimicrobial classes’The screening is a tool taking part of a strategy to prevent the spread of MDR organisms which needs to take into account the local epidemiology with different strategies function of sporadic of endemic circumstances [15]. However, systematic screening isn’t implanted in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…One of the methods used by various authors and authorities to characterize organisms as MDR is based on in vitro antimicrobial susceptibility test results, when they test ‘resistant to multiple antimicrobial agents, classes or subclasses of antimicrobial agents’ [9,10]. The definition most frequently used for multiresistant Gram-positive [11] and Gram-negative [1214] bacteria is ‘resistant to three or more antimicrobial classes’The screening is a tool taking part of a strategy to prevent the spread of MDR organisms which needs to take into account the local epidemiology with different strategies function of sporadic of endemic circumstances [15]. However, systematic screening isn’t implanted in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are important ways in which home HD differs from in-center HD that may substantially alter the risks associated with CVC use. Patients undergoing in-center HD have three times per week exposure to dialysis facilities, in which they come into contact with other chronically ill patients as well as facility staff members, presenting opportunities for exposure to exogenous organisms, including multidrug-resistant organisms (23)(24)(25). Although rates of colonization with multidrugresistant organisms are unknown in patients undergoing home HD, it is plausible that less frequent contact with health care facilities would result in less frequent colonization and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Other short-term prospective studies documented new acquisition of ceftazidime-resistant (CAZ r ) GNB in 22 of 86 (25.6%) colonized surgical intensive care unit patients during their stay over the 5-month study period (10) and new acquisition of VRE in 6 of 32 (19%) chronic hemodialysis patients for whom cultures were obtained every 5 days until discharge (9). A more recent prospective study with hemodialysis patients found that 22 (40%) of the 55 who had follow-up cultures acquired a new ARO, with totals of 20, 15, and 13% of patients acquiring MDR GNB, VRE, and MRSA, respectively (27). The main objective of this prospective study was to further characterize new acquisition of multiple AROs in communitybased SNFs, with a focus on defining the time to acquisition and persistence of colonization.…”
mentioning
confidence: 99%